Pengembangan Lembar Kerja Siswa (LKS) Berbasis Model Inkuiri Terbimbing Pada Tema Bahaya Air Yang Tercemar Untuk Menumbuhkan Berpikir Kreatif Siswa - Chyntia Wulan Aprilia; Lulu Tunjung Biru; Â Vica Dian Aprelia Resti (UNIB Press, 2023)
Development of Student Worksheets (LKS) based on guided inquiry models on the theme of the dangers of polluted water to foster students' creative thinking begins with a problem during interview with a science teacher that textbooks alone are not capable of helping students grow creative thinking, students still lack a role in learning process. This development is a worksheet which contains the steps of the learning quided inquiry model contained in the content section of the worksheet which contains problem formulation, making hypotheses, designing experiments with work steps, conducting experiments to obtain data and making conclusions so that it can help foster students' creative thinking abilities. This research is a research and development (Research & Development) using four-D (4-D) research model and a modified Thiagarajan research design because the dissiminate stage was not carried out. The results showed that the development of guided inquiry-based student worksheets on the theme of the dangers of polluted water to foster students' creative thinking was carried out through 3 stages, namely the defining stage (Define), the design stage (Design), and the development stage (Develop). The level of validity successively scores 80% with valid criteria based on the validation of material and media experts and 85% with very valid criteria and teacher's assessment gets a score of 92% with very valid criteria. Based on the results of the overall validity test, an average value of 85.6% is obtained with very valid criteria.